2005
DOI: 10.1177/0013161x04269594
|View full text |Cite
|
Sign up to set email alerts
|

Managing Community: Professional Community in Charter Schools Operated by Educational Management Organizations

Abstract: This article examines ways in which entities external to schools, in this case for-profit educational management organizations (EMOs), can influence development of school professional community. Drawing on case studies of six charter schools operated by three EMOs, we examine the five elements of professional community described by Kruse, Louis, and Bryk; supports and barriers to development of professional community; and the role of EMOs in influencing supports and barriers. We found that in these cases, EMO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 15 publications
3
24
0
1
Order By: Relevance
“…This study confirms Bulkley and Hicks's (2005) results that suggested EMOs are able to develop and maintain professional communities needed for improved student outcomes. Although a common critique is that EMO schools allocate fewer funds to instruction, this study found that this might not be the case and that EMOs just allocate differently.…”
Section: Lack Of Bureaucratic Controlsupporting
confidence: 88%
See 2 more Smart Citations
“…This study confirms Bulkley and Hicks's (2005) results that suggested EMOs are able to develop and maintain professional communities needed for improved student outcomes. Although a common critique is that EMO schools allocate fewer funds to instruction, this study found that this might not be the case and that EMOs just allocate differently.…”
Section: Lack Of Bureaucratic Controlsupporting
confidence: 88%
“…According to Bulkley and Hicks (2005), EMOs "may aid schools struggling for a sense of purpose by providing them with new resources and education and organizational vision and expertise" (p. 307), among other community-related influences. Findings from this comparative case study, which analyzed six different schools operated by three EMOs, suggest that when done well, EMOs can have a significant effect on creating a strong professional community.…”
Section: Lack Of Bureaucratic Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…On the factor of professional learning community, educational researchers such as Bryk et al (1999) and Kruse et al (1995 cited in Bulkley andHicks. 2005) specified that professional learning community of schools consisted of 5 major factors as follows: (1) shared norms and values, (2) collective focus on students' learning, (3) collaboration, (4) de-privatized practice, and (5) reflective dialogue.…”
Section: Literaturementioning
confidence: 99%
“…Its definition consists of 2 parts: Process including sharing and discussion, asking and critiquing, reflection and collaboration of shared power for work practice; the part of expected outcome in work practice (Intanam, 2010). Bryk et al (1999) and Kruse et al (1995 cited in Bulkley andHicks, 2005) specified that professional learning community of school consisted of 5 major factors as follows: (1) the shared norms and values, (2) collective focus on student learning, (3) collaboration, (4) deprivatized practice, and (5) reflective dialogue. These factors are not in hierarchy.…”
Section: Introductionmentioning
confidence: 99%